2009
DOI: 10.1039/b904068d
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-modulated metamagnetism in a nickel(ii) coordination polymer with mixed azide and carboxylate bridges

Abstract: A novel 2D coordination polymer consisting of ferromagnetic Ni(ii) chains with alternating double EO-azide bridges and (EO-azide)bis(carboxylate) triple bridges exhibits solvent-modulated metamagnetism, and the reversible dehydration/hydration processes are accompanied by significant changes in critical temperature, critical field and hysteresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Among the various types of molecular-based magnets, metal–organic frameworks (MOFs) could represent a potential model system because of their numerous metal clusters within a microporous crystalline structure, their varied functionality (via ligand and metal cluster exchange), and/or their controllable cluster–cluster interactions through tunable pore size and structure. , Moreover, open-metal sites (OMSs; unpaired electrons in the metal cluster) in MOFs are very useful for understanding the influence of unpaired electrons on magnetic metal ions, by the design of interior structures in the frameworks. , For example, the antiferro- and ferromagnetic (AFM and FM, respectively) coupling effects on metal spin centers in OMSs can therefore be elucidated via the gradual occupation of unpaired electrons at OMSs. Moreover, the spin canting and metamagnetism are particular types of AFM coupling effects in some low-dimensional [layers, two-dimensional (2D); chains, one-dimensional (1D)] systems. Because the metamagnetism disrupts the AFM ordering and turns into the FM state when a certain external field is applied, FM and canted AFM couplings should be coexist in interchain interactions with intrachain interactions. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various types of molecular-based magnets, metal–organic frameworks (MOFs) could represent a potential model system because of their numerous metal clusters within a microporous crystalline structure, their varied functionality (via ligand and metal cluster exchange), and/or their controllable cluster–cluster interactions through tunable pore size and structure. , Moreover, open-metal sites (OMSs; unpaired electrons in the metal cluster) in MOFs are very useful for understanding the influence of unpaired electrons on magnetic metal ions, by the design of interior structures in the frameworks. , For example, the antiferro- and ferromagnetic (AFM and FM, respectively) coupling effects on metal spin centers in OMSs can therefore be elucidated via the gradual occupation of unpaired electrons at OMSs. Moreover, the spin canting and metamagnetism are particular types of AFM coupling effects in some low-dimensional [layers, two-dimensional (2D); chains, one-dimensional (1D)] systems. Because the metamagnetism disrupts the AFM ordering and turns into the FM state when a certain external field is applied, FM and canted AFM couplings should be coexist in interchain interactions with intrachain interactions. , …”
mentioning
confidence: 99%
“…In this study, the feasibility of modulating magnetic phases between AFM and FM orderings is therefore explored, as suggested by the literature, by adjusting the coordination of the metal ions, solvents, or organic ligands. Furthermore, the critical temperaturesNéel temperature ( T N ) for AFM ordering and Curie temperature ( T C ) for FM orderingand the critical field ( H cr ) for the metamagnetism transition can be designed as the FM/AFM ratio in the system.…”
mentioning
confidence: 99%
“…In molecular magnetism, metamagnets are a special type of magnetic material in which two magnetic motifs (which may be a molecule, a one-dimensional (1D) chain, or a two-dimensional (2D) layer) interact antiferromagnetically (AF) through weak intermotif (molecule or chain or layer) interactions and the application of a DC field above a certain critical field ( H C ) can alter this weak AF coupling into a ferromagnetic (FM) one at low temperatures ( T N ). , Such coexistence of AF and FM in a material is difficult to predict and, consequently, highly challenging to design, but it may have significant applications in technologies associated with magnetic cooling and the magnetocaloric effect . This magnetic-field-induced first-order transition from AF to FM is critically dependent on the weak intermotif interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [43] have reported a novel 2D coordination polymer 1 (Figure 5 Liu et al [44] have successfully synthesized a high nuclearity cubic cage involving 64 Fe 3+ ions (Figure 6), which displays strong antiferromagnetism (Figure 7). They also demonstrate that the combination of the small stereohindrance HCOO − and polypodal ligands can obtain high nuclearity magnetic clusters in order to explore their novel and interesting magnetism.…”
Section: Magnetic Metal-organic Frameworkmentioning
confidence: 99%